PENGGUNAAN E-LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR - Lovandri Dwanda Putra; Annisa Nur Savitri; Ilma Nurnafi'a; Intan Ratna Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the use of E-learning to increase the interest of elementary school students. The purpose of this article is to determine the effect of using Google Classroom-based E-learning media on elementary school students' interest in learning. Great student learning interests can encourage teachers to be more creative and innovative in making learning media. The use of interesting and interactive learning media increases student interest in the learning process. The method of library research and survey articles uses references to national and international journals or articles and interviews with the 4th grade teacher of SDN 07 Metro Pusat Lampung. The survey results of the use of E-learning in class 4 of SDN 07 Metro Pusat Lampung show that using E-learning in the classroom can increase student interest in learning.